Mangrove Clam Genus Geloina: A Comprehensive Review of Biology - Thi Thu Thao, Ngo; Singano , Atupele Ellen (Journal of Fisheries and Environment, 2024)
The mangrove clam or mud clam genus Geloina is a vital component of tropical mangrove ecosystems, significantly contributing to their biodiversity. Geloina species display remarkable tolerance, enabling them to thrive across a broad spectrum of salinity levels. They are found in muddy, brackish, and even nearly freshwater regions within mangrove swamps. Mangrove clam Geloina possesses favorable characteristics for marine culture, as they are easy to cultivate. Due to their unique ecological attributes, Geloina clams emerge as objective species for fostering eco-friendly aquaculture. However, environmental factors affecting Geloina species must be considered at all time. The spawning activities of Geloina clams occure almost year around in tropical countries.With broodstock shell lengths of 68.61 and 58.63 mm, the estimated fecundity of Geloina clams ranged from 0.3185×106 to 4.416×106 oocytes. However, larval survival rate is compromised due to many environmental factors. Therefore, the life cycle and growth performance of mangrove clams should be focal points in upcoming studies to explore efficient techniques for seed production and aquaculture practices. This article also addresses these ecological challenges by comprehensively examining the natural science related to Geloina species, focusing on Southeast Asia with Vietnam as a primary focal point. Furthermore, in the strategy towards sustainable resource management, this review also discusses the incorporation of the biological characteristics of Geloina species into extractive aquaculture practices. The information regarding maturation, spawning of broodstock, and specific biological conditions for mangrove clams from this review is valuable for the resource management and aquaculture practices.